Implementation of telegram bots for user management on radius servers with captive portal - jeri purwanto (NAROTAMA UNIVERSITY, 2022)
The use of the internet has become an important requirement in all fields. The internet is accessed in an educational environment, home, office, even in a coffee shop that has a sport hostpot. The development of technology as it is currently making an agreement for hotspot users becomes necessary to use these facilities for internet purposes, while general cable technology cannot be defeated by wireless technology. In this day and age the use of networks using hotspots we have encountered in various public places and users become quite free in internet access. Wireless technology provides comfort and convenience that is quite high and comfortable to use. While in a wireless hotspot, users can access the internet anywhere. To create a network that is connected to a secure internet, we can create a system using Radius Server to authorize and authenticate on the network, manage the use of each user on the network. Telegram BOT is an API (application programming interface) that allows one to integrate two different applications from applications and websites, in this case the Telegram chat application with other devices. So the telegram chat that can be done by humans (users) with this telegram BOT, then the chat bias can be replied with the program.